Tumor-targeted delivery of lnc antisense RNA against RCAS1 by live-attenuated tryptophan-auxotrophic Salmonella inhibited 4T1 breast tumors and metastasis in mice - Chandran Sivasankar; Chamith Hewawaduge; Pandiyan Muthuramalingam; John Hwa Lee (Elsevier, 2023)
Emerging chemo- and radiotherapy resistance exacerbated the cancer risk and necessitated novel treatment strategies. Although RNA therapeutics against pro-oncogenic genes are highly effective, tumor-specific delivery remains a barrier to the implementation of this valuable tool. In this study, we report a tryptophan-auxotrophic Salmonella typhimurium strain as an onco-therapeutic delivery system with tumor-targeting ability using 4T1 mice breast-cancer model. The receptor-binding cancer antigen expressed on SiSo cell (RCAS1) is a cancer-specific protein that induces the apoptosis of peripheral lymphocytes and confers tumor immune evasion. We designed a long non-coding antisense-RNA against RCAS1 (asRCAS1) and delivered by Salmonella using a non-antibiotic, auxotrophic-selective, eukaryotic expression plasmid, pJHL204. After in vivo tumor-to-tumor passaging, the JOL2888 (ΔtrpA, ΔtrpE, Δasd + asRCAS1) strain exhibited high sustainability in tumors, but did not last in healthy organs, thereby demonstrating tumor specificity and safety. RCAS1 inhibition in the tumor was confirmed by western blotting and qPCR. In mice, JOL2888 treatment reduced tumor-associated macrophages, improved the T cell population, elicited cell-mediated immunity, and suppressed cancer-promoting genes. Consequently, the JOL2888 treatment significantly decreased the tumor volume by 80%, decreased splenomegaly by 30%, and completely arrested lung metastasis. These findings highlight the intrinsic tumor-targeting ability of tryptophan-auxotrophic Salmonella for delivering onco-therapeutic macromolecules.